The LGBTQI health forum: an innovative interprofessional initiative to support curriculum reform. Issue 1 (1st January 2017) - Braun, Hannan M.; Ramirez, David; Zahner, Greg J.; Gillis-Buck, Eva Mae; Sheriff, Heather; Ferrone, Marcus
ABSTRACT: Lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI) individuals continue to face barriers to accessing appropriate and comprehensive healthcare. Compounding this problem, healthcare trainees report few training opportunities and low levels of preparedness to care for LGBTQI patients. In 2009, an interprofessional group of students and a faculty advisor at the University of California, San Francisco, developed a novel student-organized LGBTQI Health Forum for medical, dental, pharmacy, nursing, and physical therapy students to deliver LGBTQI health content that was otherwise absent from the formal curriculum. This elective course has evolved based upon participant feedback, emerging educational strategies, and the existing curricula infrastructure at our institution. After eight years of growth, this 10-contact hour weekend elective attracts over 250 participants each year. Plenary sessions deliver foundational terminology and skills to all attendees. Learners then select breakout sessions to attend, allowing for an individualized curriculum based upon specific interests and knowledge gaps. Breakout session topics prioritize traditionally underrepresented aspects of LGBTQI health in professional school curricula. This Forum serves as a model in which to supplement LGBTQI content into existing school curricula and offers an opportunity for interprofessional education. Next steps include conducting a formal evaluation of the curriculum, expanding our performance-based assessments, and potentially implementing a continuing education program for licensed practitioners. With a core group of interprofessional student organizers and a faculty champion, other institutions may view this course architecture as a potential way to offer learners not only LGBTQI content, but other underrepresented subjects into their own educational programs.